Perceived insufficient pedagogical content knowledge in teaching movement and physical activity. Experiences from an action-oriented study among educators in early childhood education and care - Sollerhed, Ann-Christin (Frontiers in Sports and Active Living, 2023)
Movement and physical activity (MoPA) are critical to children's health and development. Many children aged 1–5 years are enrolled in Early Childhood Education and Care (ECEC) in Sweden, and high expectations are placed on educators to deliver education of sufficient quality to support children's development. The aim of the 18-month-long action-based study was to investigate how 88 ECEC educators in five preschools perceived and experienced the priority and teaching of MoPA. The educators planned and implemented MoPA sessions among children. They filmed sequences from the sessions, which were shown in the focus groups and were the starting point for the collegial discussions. Content analysis of the focus group discussions revealed three themes: Teaching aspects; Educational aspects; Structural aspects, with associated subthemes. During the project with the trial-and-error MoPA teaching, the educators detected insufficient PCK to teach MoPA and that teaching was often replaced with free play. Increased metacognition made the educators aware of children's different MoPA levels and that free play did not always increase all children's skills. The perceived insufficient pedagogical content knowledge to teach MoPA was perceived as a troublesome barrier for promoting MoPA. During the project, the educators' metacognition about MoPA increased, which made the educators aware of children's different MoPA levels and that free play did not always increase all children's skills. Despite of increased metacognition, most of the educators were not ready to leave their comfort zones and were not open to extra work or effort when it came to MoPA. However, the educators demonstrated the need for improved education in MoPA in early childhood teacher education, as well as the need for continuous education for working educators in ECEC to enhance the pedagogic content knowledge for adequate teaching in MoPA, which is important for children's present development and future health.